Assessing the Impact of ICT, Tourism, Globalization and Urbanization on Environmental Degradation and Economic Growth - Asma Parveen; Kashif Mehmood; Maryam Javed (NUML International Journal of Business & Management)
This study explores the impact of information and communication technology (ICT), tourism, globalization, and urbanization on the economic growth and environmental degradation of middle-income countries classified as overall, upper and lower-middle-income countries. It uses a micro panel dataset of 65 nations from 2000 to 2021 through a two-step Generalized Method of Moment estimation approach.   The results indicate that the influence of ICT on environmental degradation differs across nation groups. Overall countries have a harmful effect, upper-middle countries exhibit a beneficial influence, and lower-middle countries show no significant link. Tourism continually causes environmental deterioration in all sorts of nations, emphasizing the need for eco-friendly tourist initiatives.   Globalization has been seen to have a positive correlation with environmental degradation in countries classified as Overall and Upper-middle income, but a negative correlation in Lower-middle-income nations.   Urbanization has a favorable influence on environmental deterioration in Overall and Lower-middle-income nations, but it does not have a significant impact in Upper-middle-income countries.  These findings underscore the need to tackle the environmental impacts of information and communication technology (ICT), tourism, globalization, and urbanization. To attain a greener and more sustainable future while fostering economic growth, policymakers should prioritize sustainable development, introduce energy-efficient technologies, encourage responsible tourism practices, enforce environmental regulations, and advocate for inclusive urban planning.